MODELS OF SUSTAINABLE USE OF WILD MEDICAL PLANTS IN W. BALKAN (SE EUROPE) - Redzic, S.; Barudanovic, S.; Basic, H. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Due to the past extensive and random use of wild medicinal plants in this territory - including the western Balkan countries (SE Europe) - those plants are significantly endangered. Many of them even appeared on “red lists of endangered floras” [1]. In order to preserve natural gene-funds of medicinal plants, it is necessary to set methods and models that would result in sustainable models for their use. Sustainability would be achieved by exploitng the biomass from natural populations with respect of the biological and ecological characteristics of given plant species and if possible according to the market requirements. This approach includes the determination of variables that could be used as a basis for the development of mathematical and statistical models in order to reach “function of sustainability”. Sustainable function implies results of two key variables, production of biomass of given medicinal plants and amount of biomass that is used or is exploited in natural populations. The graphic model for that function is diversified and it largely depends on the plant species, the used part of the plant, the vegetation season, the ecological circumstances in which the given plant is being developed, the form of picking, the total anthropogenic pressure of cutter, the pasture, the wood cutting and the global changes. This ecological statistical approach is applied to several species of medicinal plants that are intensively exploited in the Western Balkan [2, 3]. In the Mediterranean belt, it is Salvia officinalis, in the Mediterranean and sub-Mediterranean belt it is the species Helichrysum italicum, in the Mediterranean mountain belt they are the species Satureja montana and Satureja subspicata, in the mountain belt they are the species Gentiana lutea subsp. symphyandra and Arctostaphyllos uva-ursi, and in the belt of the deciduous forests, it is the species Atropa belladonna. Research shows that the gradient of sustainable use is different in different belts. In the Mediterranean and sub-Mediterranean belt it is about 50%, in the mountain belt it is 30 %, while in the belt of forests it is up to 70 % (per km2). That means it is necessary to leave about 50 % of units of sage in free nature, approximately the same number of units of the order Satureja, about 70 % of units of Gentian and about 30 % of biomass of the species Atropa belladonna in order to reach the effect of sustainability. This approach is beneficial for the protection of medicinal plants and could be used as a practical instrument in reaching organic production and certification of medicinal and aromatic wild plants. References: 1. Redzic S (2006) Proc 1st IFOAM Intern Conf Organic Wild Production, 117-141. 2. Redzic SS (2007) Coll. Antropol. 31: 869-890. 3. Redzic SJ (2006) Ecol. Food & Nutr. 45: 189-232.